Urbanisation effect on dengue cases in Hulu Langat, Selangor (2014-2018) - Mohd Tohit, Nor Faiza; Ramli, Lina Farhana; Salleh, Rosilawati; Suli, Zaliza; H, M Nasir; Husam, Abdullah (2019)
INTRODUCTION: The frequency and magnitude of epidemic disease continued to increase in tandem with rapid urbanization. Mosquitoes carrying the dengue virus can increase following unplanned and unhealthy urbanization. In the large urban regions, crowded human populations live in intimate association with equally large mosquito populations provides the ideal home for maintenance of the viruses and the periodic generation of epidemic strains.